2008
DOI: 10.4049/jimmunol.180.5.3578
|View full text |Cite
|
Sign up to set email alerts
|

Questionable Relevance of γδ T Lymphocytes in Renal Cell Carcinoma

Abstract: Adoptive γδ T cell immunotherapy has moved briskly into clinical trials prompted by several small studies suggesting abundant accumulation of γδ T cells within renal cell carcinoma (RCC). In this study, we re-examined levels of γδ T cells within RCC tumors and correlated levels of these cells with pathologic features and outcome associated with this form of cancer. Tissues from 248 consecutive clear cell RCC tumors obtained from 2000 to 2003 were stained and quantified for total CD3+ and γδ T cells per mm2. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…This result was also in accordance with the low levels of intratumoral γδ T cells in other solid tumors, such as renal cancer (Kowalczyk et al, 1996;Inman et al, 2008). In the tumoral tissues, we found that the number of γδ T cells was positively associated with OS when patients were defined as following subgroups: patients with earlystage (BCLC stage A) HCC, or with single tumor, or with well differentiated tumor, or without thrombi, which indicated that the important antitumor role of γδ T cells in early-stage HCC.…”
Section: Discussionsupporting
confidence: 72%
“…This result was also in accordance with the low levels of intratumoral γδ T cells in other solid tumors, such as renal cancer (Kowalczyk et al, 1996;Inman et al, 2008). In the tumoral tissues, we found that the number of γδ T cells was positively associated with OS when patients were defined as following subgroups: patients with earlystage (BCLC stage A) HCC, or with single tumor, or with well differentiated tumor, or without thrombi, which indicated that the important antitumor role of γδ T cells in early-stage HCC.…”
Section: Discussionsupporting
confidence: 72%
“…[5][6][7] cd TILs, primarily of the Vc9Vd2 cd T cell type, were reported in renal cell carcinomas, albeit with controversial prognostic values. [7][8][9][10] Nasopharyngeal carcinoma patients carry Vc9Vd2 cd T lymphocytes that are functionally impaired in blood 11 but are able to infiltrate and reduce xenografted nasopharyngeal tumors in mice. 12 Likewise, orthotopic xenografts of breast tumors 13 or bladder carcinomas 14 in mice infused with human TCRVc9Vd2 1 lymphocytes also show strong tumor infiltration by cd TILs and subsequent arrest of tumor growth.…”
Section: Rationale For Harnessing CD Cells In Cancer Immunotherapymentioning
confidence: 99%
“…gd TILs isolated in various types of cancer, including colorectal, breast, prostate, ovarian and RCC [17,24,25], recognize and kill both the autologous tumor and a broad range of related tumors, presumably via the recognition of shared stress-related ligands, but do not kill nontransformed cells [17,25]. The infiltration of Vg1 and Vd1 gd T cells into necrotizing melanomas (NMMs) significantly correlates with increased survival [26], whereas intratumoral gd T cell infiltration in RCC tumors does not [27]. These studies suggest that gd T cell infiltration might be beneficial; however, the immunoregulatory properties of gd T cells should not be ignored [28].…”
mentioning
confidence: 97%